2022
DOI: 10.1590/2175-8239-jbn-2020-0246
|View full text |Cite
|
Sign up to set email alerts
|

Xanthogranulomatous pyelonephritis in a pediatric patient

Abstract: Introduction: Xanthogranulomatous pyelonephritis consists of a chronic infectious and inflammatory process of the renal parenchyma, a variant of chronic obstructive pyelonephritis. It is more prevalent in middle-aged adults, rare in pediatric patients, with less than 300 cases reported in children worldwide. Report: Preschooler, aged 2 years and 11 months, male, with 2 months of abdominal distention, increased temperature and intense pallor, associated with microcytic anemia refractory to the use of ferrous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Physical examination may reveal fever, pallor due to anemia, palpable unilateral or bilateral renal mass, costovertebral angle tenderness, nephrocutaneous fistulas, and rarely hepatomegaly due to liver invasion (3). Karabulut et al (9) reported abdominal pain, weight loss and pallor; and Caixeta et al (10) reported fever, pallor, and abdominal distension in their papers. In our patient, the initial complaints were fever, abdominal pain, weakness, and pallor, similarly.…”
Section: Discussionmentioning
confidence: 98%
“…Physical examination may reveal fever, pallor due to anemia, palpable unilateral or bilateral renal mass, costovertebral angle tenderness, nephrocutaneous fistulas, and rarely hepatomegaly due to liver invasion (3). Karabulut et al (9) reported abdominal pain, weight loss and pallor; and Caixeta et al (10) reported fever, pallor, and abdominal distension in their papers. In our patient, the initial complaints were fever, abdominal pain, weakness, and pallor, similarly.…”
Section: Discussionmentioning
confidence: 98%
“…XGP is an uncommon presentation in children and incorporates less than 1% of chronic pyelonephritis 2 3. It involves a chronic suppurative process of unknown pathogenesis that leads to destruction of renal parenchyma and replacement with granulomatous tissue, leading to a non-functional kidney4 (figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…It involves a chronic suppurative process of unknown pathogenesis that leads to destruction of renal parenchyma and replacement with granulomatous tissue, leading to a non-functional kidney4 (figure 4). Clinical presentation is non-specific and often includes abdominal distension, abdominal pain, fever, malaise and anorexia 2 3 5. Laboratory investigations often show raised inflammatory markers, anaemia, thrombocytopenia, but normal renal function if the opposite kidney is unaffected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is most common among women of age 40–60 years and is seen only sporadically in children with just less than 300 cases reported worldwide to date 1. The age of onset varies (21 days to 16 years), although 60%–75% of cases have been diagnosed before 5 years of age 2. Neonatal cases are exceptionally rare, with only two cases reported in the literature 3 4.…”
Section: Introductionmentioning
confidence: 99%